Implementasi Green Marketing Mix dalam Pengelolaan Green Masjid: Studi Kasus Masjid Nurul Jannah Petrokimia Gresik - Musyanto, Moch Herma (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2023)
This research explores the implementation of green marketing mix in the management of Green Mosque, especially in Nurul Jannah Mosque of PT Petrokimia Gresik. Using explorative qualitative method, this research focuses on 4P green marketing mix strategy (green Product, green Price, green Place, green Promotion). The results show that green products, such as green buildings and areas, not only save electricity and water but also create alternative income and community empowerment. The green price mainly comes from the sale of garden produce and fish ponds, with donations from the congregation as a contribution. Green premises include the mosque and the entire green area for transactions with congregants. In terms of promotion, active and passive methods are used to introduce programs and products to the community. The implementation of green marketing mix in the management of the Green Mosque improves management professionalism, designs products according to customer needs, and communicates effectively. This innovation can be duplicated to make a real contribution to global environmental conservation efforts.